Gut feelings: gastrointestinal signs in French bulldogs undergoing spinal surgery - du Toit, Michelle; Motta, Luca (Frontiers in Veterinary Science, 2024)
IntroductionThe French bulldog (FBD) is a brachycephalic breed prone to several neurological conditions, of which intervertebral disc herniation (IVDH) is considerably prevalent. Gastrointestinal (GI) disease is a reported complication in dogs surgically treated for IVDH. The objective of this study was to describe GI signs and their outcome in FBDs surgically treated for IVDH.Materials and methodsData regarding the GI signs (vomiting, diarrhoea and regurgitation), their frequency and short-term outcome in FBDs surgically treated for IVDH (cervical, thoracolumbar or lumbar) between January 2017 and April 2023 were obtained from medical records at one institution. Categorical variables were compared using Fisher exact tests, and ordinal/continuous data between categorical groups using Kruskal-Wallis or Mann-Whitney tests.ResultsNinety-seven FBDs were included for analysis. GI signs occurred in 74/97 (76.3%) FBDs while hospitalised, with 33.8% and 66.2% developing GI signs pre- and post-operatively, respectively. FBDs that developed GI signs had a mean of 4.9 episodes. Diarrhoea was the most common GI sign encountered (51/74) compared to regurgitation (38/74) and vomiting (22/74). Resolution of GI signs occurred within a mean of 2.2 days. Mean duration of hospitalisation post-surgery was 4.6 days in FBDs that developed GI signs versus 3.7 days in FBDs that did not (p = 0.033). Anaesthesia length was associated with developing GI signs (p=0.037). Neurological severity, neuroanatomical localisation and surgical procedure were not associated with development of GI signs (p = 0.42, p = 0.794 and p = 1, respectively).ConclusionGI signs were commonly encountered in FBDs surgically treated for IVDH and associated with length of anaesthesia and prolonged hospitalisation.